2010
DOI: 10.1093/hmg/ddq474
|View full text |Cite
|
Sign up to set email alerts
|

ELF1 is associated with systemic lupus erythematosus in Asian populations

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease with a strong genetic involvement. The susceptibility genes identified so far can only explain a small proportion of disease heritability. Through a genome-wide association in a Hong Kong Chinese cohort and subsequent replication in two other Asian populations, with a total of 3164 patients and 4482 matched controls, we identified association of ELF1 (E74-like factor 1) with SLE (rs7329174, OR = 1.26, joint P= 1.47 × 10(-8)). ELF1 belongs to the ETS f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 52 publications
2
42
0
Order By: Relevance
“…In addition, IL12A and CXCR5 were identified as new loci for Sjögren's syndrome susceptibility. Except for CXCR5, the majority of the genes identified in this study are well-known risk loci for SLE susceptibility [89] underscoring the close relationship between both diseases (Fig. 1).…”
Section: Genetics Of Sjö Gren's Syndromementioning
confidence: 52%
“…In addition, IL12A and CXCR5 were identified as new loci for Sjögren's syndrome susceptibility. Except for CXCR5, the majority of the genes identified in this study are well-known risk loci for SLE susceptibility [89] underscoring the close relationship between both diseases (Fig. 1).…”
Section: Genetics Of Sjö Gren's Syndromementioning
confidence: 52%
“…The ethnic and genetic heterogeneity may contribute to the susceptibility and complex clinical manifestation in SLE. Nine GWAS of SLE have been published, which identified more than 30 susceptibility genes or loci for SLE and confirmed some of genes found by candidate gene study [36][37][38][39][40][41][42][43][44]. These susceptibility genes for SLE included HLA [37][38][39][40]45], IRF5 [37][38][39][40]45], TNFAIP3 [37,40,45], BLK [37,39,40,45], STAT4 [37][38][39][40]45], ITGAM [38,39], PTPN22 [38,40], PHRF1 (also called KIAA1542) [38,40], TNFSF4 (also called OX40L) [38,40], BANK1 [36], PRDM1 [40,45], ATG5 [38,40], PTTG1 [38], PXK [38], FCGR2A [38], HIC2 …”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 84%
“…In recent years, understanding of SLE’s genetic etiology has been transformed by GWASs, with the largest study in Europeans3 (4,036 cases and 6,959 controls) finding evidence of association at 41 autosomal loci. Meanwhile, two published GWASs4,5 in Chinese populations and follow-up studies in Asians610 found association at 31 loci, 11 of which are not published for Europeans. Thus 52 SLE disease-susceptibility autosomal loci have been mapped by GWASs in these two populations.…”
mentioning
confidence: 99%